Impact of the Quality of Postpartum Sleep and its Health Determinants on Human Milk Volume. Issue 5 (September 2020) - Carrega, Joanna; Lee, Shih-Yu; Clark, Patricia; Cranford, Joan; Lloyd, Steven
Abstract: Purpose: To examine the impact of postpartum sleep disturbance on 24-hour milk volume and breastfeeding during the early postpartum period. Factors associated with postpartum sleep disturbance also were examined. Study Design and Methods: A descriptive, correlational design was used. The sample included 29 first-time mothers exclusively breastfeeding healthy, full-term newborns. A home visit was conducted to collect self-report data for sleep, stress, fatigue, depression, and anxiety at 2 weeks postpartum. Infant test weights as an estimate of 24-hour milk volume also were performed. At 1 month, a phone interview was conducted for breastfeeding status. Pearson's correlation and hierarchical regression were used for data analysis. Results: All mothers were breastfeeding at 2 weeks and at 1 month postpartum. Most (69.2%) reported significant sleep disturbance. Higher degree of stress was associated with more disturbed sleep ( β = .59, p = .001), and sleep disturbance was associated with more symptoms of fatigue ( r = .70, p = - .001), depression ( r = .58, p = .001), and anxiety ( r = .52, p = - .01). Poor sleep quality was the only significant predictor for lower milk volume ( β = - .70, p = .02). Clinical Implications: Clinically significant sleep disturbance is common during the early postpartum period and may have a negative impact on human milk production and other important maternal health indicators. A better understanding of postpartum sleep disturbance and its impact on breastfeeding and maternal health is needed. Abstract : In this study of new mothers, the relationship between sleep quality and breast milk volume was explored. Most women reported substantial sleep disturbance during the first month postpartum. Poor sleep quality was a significant predictor for lower milk volume.